A comparison of market landings during fish spawning seasons to better understand the effectiveness of the temporal fishery closure in Turkey. (1st December 2020) - Yıldız, Taner; Ulman, Aylin; Demirel, Nazli
Abstract: Seasonal fishery closures, are an input control measure to reduce fishing pressure on spawning stocks in fisheries management. Despite the huge foregone economic losses from such closures, the efficacy of them has yet to be examined in Turkey. This study compares the monthly landed catch distribution for commercial marine species averaged for 12 years (2006–2017) from Istanbul fish market, to catch rates of those species during the spawning seasons. Our results revealed that at first glance, most commercially important fish species examined here have their spawning seasons protected under the Turkish industrial seasonal closure period, especially for small and medium pelagics, as well as some demersals. On the other hand, taxa with winter spawning seasons such as Merlangius merlangus, John dory Zeus faber, brown meagre Sciaena umbra, big-scale sand smelt Atherina boyeri, and bogue Boops boops do not benefit from the commercial fisheries summer closure (>50% of their catch total). Also, some species are still heavily fished (>35% of their catch total) during the closure implying they are mainly targeted by small-scale fisheries (SSF). To help rebuild the commercial fisheries, we recommend the accompaniment of the industrial closure with the use of 'Real Time Closures' (RTCs) applied to all fishing sectors for species highly fished during their spawning periods and spawning habitats. Graphical abstract: Image 1 Highlights: 12 years of Istanbul fish market monthly landings data are analyzed. Spawning seasons to gauge effectiveness of the commercial fishing ban are compared. Spawning seasons of most commercial fish overlap with the seasonal closure period. Swordfish, brown meagre and white grouper are heavily landed during closure period. Seven fish species need specific temporal closures during their spawning periods.